2005
DOI: 10.1111/j.1439-0310.2005.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Occurrence of Preference Functions and Acceptance Thresholds in Female Choice: Mate Discrimination in the Lesser Wax Moth

Abstract: Basic economic models adapted from foraging theory predict that decisions in mate choice may be determined either by Ôbest-of-nÕ preference functions or by sequential rules incorporating acceptance thresholds. However, in some species, more complex determinations that incorporate versions of both protocols are found. To understand the functions of co-occurring protocols, we studied mating decisions in the lesser wax moth, Achroia grisella (Lepidoptera: Pyralidae), an acoustic species in which females prefer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…They observed a much stronger preference for large size when alternatives were presented in a paired fashion rather than sequentially, suggesting that females applied comparative decision rules only when simultaneous evaluation was possible. Brandt et al (2005) showed that lesser wax moth females, Achroia grisella, used both absolute and relative criteria to choose their mates: independent of the number of available prospective mates, they rejected mates that call at a rate lower than a fixed threshold, but, when several males called above the acceptance threshold, females chose the one with the highest rate.…”
Section: Does Variation In the Pattern Of Choice Reflect Variation Inmentioning
confidence: 99%
“…They observed a much stronger preference for large size when alternatives were presented in a paired fashion rather than sequentially, suggesting that females applied comparative decision rules only when simultaneous evaluation was possible. Brandt et al (2005) showed that lesser wax moth females, Achroia grisella, used both absolute and relative criteria to choose their mates: independent of the number of available prospective mates, they rejected mates that call at a rate lower than a fixed threshold, but, when several males called above the acceptance threshold, females chose the one with the highest rate.…”
Section: Does Variation In the Pattern Of Choice Reflect Variation Inmentioning
confidence: 99%
“…In addition to the above preference functions, which describe the way in which females might choose one male over another when given options, threshold values also exist for some of the song characters. A threshold value is most evident for pulse-pair rate, as females do not respond to male song below a certain rate (which ranges from 25 to 70 pulse pairs s -1 among females) regardless of the values of the song's other characters and even when that male is the sole one present (Brandt et al 2005). Female preference functions and threshold values may both impose directional selection on male song characters.…”
Section: Acoustic Communication and Sexual Selection In A Grisellamentioning
confidence: 99%
“…Moreover, the pulse-pair rate threshold represents a fundamental aspect of a female's behavioral response to male song, individual females vary considerably in this parameter, and it is repeatable (Jang et al 1997). Substantial overlap between the distributions of male pulse-pair rates and female pulse-pair rate thresholds often exists (Brandt et al 2005), indicating that this female response may impose directional selection on the male song character. That is, a certain percentage of males in a population will not even be considered as potential mates by a certain percentage of females.…”
Section: Measurement Of Female Responsementioning
confidence: 99%
“…A. grisella females preferentially oriented towards the calls of males that were louder, delivered sounds with higher rates and more evenly spaced pairs of pulses, and included longer pulse lengths and longer silent intervals within pairs of pulses. A male may have more attractiveness to females, if it sings with higher peak amplitudes and longer asynchrony intervals and for longer nightly periods (Brandt & Greenfi eld 2004;Brandt et al 2005). Signal preference was based on acoustic energy and the power of the male signals (Jang & Greenfi eld 1996).…”
Section: Communicationmentioning
confidence: 99%